2018
DOI: 10.1093/ndt/gfy117
|View full text |Cite
|
Sign up to set email alerts
|

Patients with advanced chronic kidney disease and vascular calcification have a large hydrodynamic radius of secondary calciprotein particles

Abstract: Rh of CPP2, but not T50, is independently associated with VC in patients with CKD Stages 4-5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 31 publications
0
38
0
2
Order By: Relevance
“…Scavenger receptor A is a major endocytosis receptor for CPP2s but not for CPP1s, indicating separate clearance pathways 24 . Native CPPs in fresh plasma are smaller and lower in density than synthetic CPP1 and CPP2 29 . In CKD, CPPs are likely involved in the pathology of VC 25,26 .…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Scavenger receptor A is a major endocytosis receptor for CPP2s but not for CPP1s, indicating separate clearance pathways 24 . Native CPPs in fresh plasma are smaller and lower in density than synthetic CPP1 and CPP2 29 . In CKD, CPPs are likely involved in the pathology of VC 25,26 .…”
mentioning
confidence: 89%
“…Serum CPP levels increase with decline of renal function and correlate with coronary artery calcification score, arterial stiffness, serum phosphate, inflammation, and procalcific factors 27,28 . Moreover, in patients with advanced CKD, the R h of CPP2 was associated with VC 29 . The fact that CPP2s have the ability to induce VSMC calcification in vitro has raised the hypothesis that CPP2s may present a valid therapeutic target in VC 30 .…”
mentioning
confidence: 94%
“…These unstructured CPPs are called secondary CPPs, and such secondary CPPs were predictive for vascular calcification and cardiovascular mortality in uremic patients (Figure 1) [65]. Clinical evidence suggested that patients with CKD and a higher concentration of secondary CPPs had a higher incidence of vascular calcification [66]. Therefore, maintaining sufficient calcification inhibitors should be a therapeutic strategy for treating vascular calcification.…”
Section: The Role Of Matrix Vesicles/exosomes and Calciprotein Particmentioning
confidence: 99%
“…Кроме того, в последних исследованиях удалось успешно детектировать КФБ в сыворотке крови пациентов с терминальной хронической почечной недостаточностью [55] и преддиализной ее стадией [56,57] при помощи проточной цитометрии с использованием специфичных к фосфату кальция и клеточным мембранам флюоресцентных маркеров [55,56] и динамического рассеяния света [57]. Проточная цитометрия при помощи аналогичного окрашивания также позволила детектировать КФБ в перитонеальном диализате пациентов с терминальной хронической почечной недостаточностью [58].…”
Section: клиническое значение кфбunclassified
“…Проточная цитометрия при помощи аналогичного окрашивания также позволила детектировать КФБ в перитонеальном диализате пациентов с терминальной хронической почечной недостаточностью [58]. Электронная и атомно-силовая микроскопия являются альтернативным методом детекции КФБ в осадке после центрифугирования сыворотки пациентов с терминальной хронической почечной недостаточностью [57,[59][60][61], однако данные методы в силу трудоемкости и относительной малодоступности едва ли могут быть применены в клинической практике.…”
Section: клиническое значение кфбunclassified